EFFECT OF SOCIO-ART WORKING GROUP THERAPY IN REDUCING THE SYMPTOMS OF HALLUCINATIONS IN COMMUNITY HEALTH CENTER - Lestari, Retno; Ahsan, Ahsan (Public Health of Indonesia, 2017)
Background: Schizophrenia is a chronic illness with considerable impact on individuals and their families. One of the symptoms of schizophrenia is hallucination. The treatment goals are reducing the symptoms and maintaining the recovery from the effects of illness.Objective: This study aimed to analyze the effect of socialization and art-working group therapy in reducing the symptoms of hallucinations.Methods: This study used a pre-experimental design with one-group pretest-posttest involved 60 patients aged between 12 and 55 years diagnosed with schizophrenia in the Community-Integrated Health Care in East Java. The Symptoms of Hallucinations Checklist was used to assess the hallucination symptoms. Data were analyzed using Wilcoxon signed rank test.Results: Findings showed that there was a statistically significance difference between pretest and posttest score after the socialization and art-working group therapy with p-value 0.000 (p<0.05).Conclusion: Socialization and art-working group therapy had a significant effect in reducing the symptoms of hallucinations in patients with schizophrenia.